Amplitude analysis of the B+ → D+D−K+ decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
Results are reported from an amplitude analysis of the B+→D+D−K+ decay. The analysis is carried out using LHCb proton-proton collision data taken at √s=7, 8, and 13 TeV, corresponding to a total integrated luminosity of 9 fb−1. In order to obtain a good description of the data, it is found to be necessary to include new spin-0 and spin-1 resonances in the D−K+ channel with masses around 2.9 GeV/c2, and a new spin-0 charmonium resonance in proximity to the spin-2 χc2(3930) state.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, A. Piucci, S. Stemmle, D.A. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 956 weitere]
Im Titel sind die Zeichen "+" und "-" jeweils hochgestellt
Gesehen am 18.02.2021